2020
DOI: 10.1001/jamaneurol.2019.4914
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cardiovascular Disease and Long-term Exposure to Air Pollution With the Risk of Dementia

Abstract: IMPORTANCE Emerging yet contrasting evidence associates air pollution with incident dementia, and the potential role of cardiovascular disease (CVD) in this association is unclear. OBJECTIVE To investigate the association between long-term exposure to air pollution and dementia and to assess the role of CVD in that association. DESIGN, SETTING, AND PARTICIPANTS Data for this cohort study were extracted from the ongoing Swedish National Study on Aging and Care in Kungsholmen (SNAC-K), a longitudinal population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 33 publications
7
175
6
2
Order By: Relevance
“…Air pollution elements such as PM 2.5 , PM 10 , NO 2 , and O 3 are known to play an important role in both infectious and non-infectious diseases (Wang et al 2019;Liu et al 2019;Grande et al 2020;Lin et al 2007;Chang et al 2020;Ciencewicki and Jaspers 2007). Some studies have also investigated the association between air pollution and incidence and distribution of COVID-19 in different other countries (Frontera et al 2020;Fattorini and Regoli 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution elements such as PM 2.5 , PM 10 , NO 2 , and O 3 are known to play an important role in both infectious and non-infectious diseases (Wang et al 2019;Liu et al 2019;Grande et al 2020;Lin et al 2007;Chang et al 2020;Ciencewicki and Jaspers 2007). Some studies have also investigated the association between air pollution and incidence and distribution of COVID-19 in different other countries (Frontera et al 2020;Fattorini and Regoli 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The risk factors for COVID-19 -associated severity and death are still under investigation, but some environmental and demographic factors such as air pollution (particle matter, nitrogen dioxide (NO 2 ), ozone (O 3 )) (Coccia 2020;Fattorini and Regoli 2020;Frontera et al 2020;Liang et al 2020), atmospheric patterns (temperature, humidity) (Sajadi et al 2020;Sarmadi et al 2020b), and comorbidities (cardiovascular and cerebrovascular disease, and cancer) (Richardson et al 2020;Tian et al 2020) might play a plausible role for both susceptibility and vulnerability of populations. The impact of mentioned parameters on excessive morbidity and mortality attributed to other respiratory or chronic diseases has been wellestablished in recent years (Liu et al 2019;Shi et al 2016;Wang et al 2019;Grande et al 2020). In order to investigate the correlation between air pollution indicators and various diseases, air quality index (AQI) can be considered as an important parameter that involves many air pollution elements.…”
Section: Introductionmentioning
confidence: 99%
“…and mega-trends in climate accompanied by extreme weather conditions makes the population becomes increasingly vulnerable. These conditions have resulted in several socioeconomic impacts, such as morbidities, mortality, migration, poverty exacerbation, violent conflict, affecting people of all ages and all nationalities (Rizzoli et al, 2019;Grande et al, 2020;Watts et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous researchers, they found that air pollution can cause heart stroke, which can later cause dementia, but more evidence was needed to prove it. And also, it was stated that there was no cure found up to date to cure dementia Choi and Kim (2019) (Choi and Kim, 2019) (Grande et al, 2020). Other researchers have also found good evidence that increased exposure to air pollution can cause dementia, especially among elderly people (Peters, 2019;Wu, 2015).…”
Section: Figure 16: Bar Chart Represents the Association Between The mentioning
confidence: 99%
“…And up to date, there is no cure found for treating dementia. And also, it was noticed that air pollution had a negative impact on human health (Grande, 2020). It was also found that there is no relation between traf ic-related noise pollution and dementia (Andersson, 2018;Carey, 2018;Paul, 2019).…”
Section: Introductionmentioning
confidence: 99%